SÁNDOR VERESS’S „THRENOS” IN THE LIGHT OF ‘TRADITION’ AND ‘RENEWAL’ - FEKETE, Miklós (Studia Universitatis Babes-Bolyai Musica, 2023)
This paper focuses on the musical analysis of Veress’s orchestral composition, Threnos. Written in 1945 and dedicated to the memory of Bartók, it is a one-movement work, divided into three independent internal sections, each of them representing an orchestral gradation. Being a threnody, Veress inserts two folk-like funeral laments, which are the composer’s melodic inventions, in the style of folk music. Veress, the ethnomusicologist and composer presents the bartókian principle of how to capture the ethos of folk music in its structure, melody, harmony, and rhythm, and how to express it in such a modern and innovative way, that a completely new quality is born from it.